Next Year in Jerusalem: Constructions of Israeli Nationalism in High Holiday Rituals - Amelia Caron (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2011)
This article explores the intersection of nationalism and Jewish identity maintenance with High Holiday celebrations carried out in the Diaspora. Using directed interviews and participant observation, I took part in the rituals of Rosh Hashanah (the Jewish New Year) and Yom Kippur (the Day of Atonement) to uncover the way that American Jews and Israelis living in the Jewish Diaspora create and sustain a dialogue with their “traditional” homeland, Israel. However, the connections between Jews and this homeland have shifted dramatically in recent times. Although Israel encourages all persons of Jewish descent to immigrate to the Holy Land, a complex web of multiple nationalities and identities is at play in the lives of Jews who live in the Diaspora. Through religious rituals, members of the Jewish faith – whether Orthodox, secular, or something in between – develop and preserve a philosophy of a world Jewish identity with surprising results. Although the rituals themselves may be used to encourage solidarity with the state of Israel, individual Jews now find themselves re-negotiating their sense of belonging. As toasts of "Next year in Jerusalem!" are made, the complexities of national loyalty, ethnicity, and religious practice merge to form a question on the lips of many Jewish people: What is a Jew, and who decides?